Práticas corporais de aventura na Educação Física escolar: uma proposta de ensino com base na metodologia crítico-superadora - Morais, Gleison Gomes de (2020)
The research presented here has as its object of study the teaching of the Corporal Adventure Practices in Physical Education classes in Elementary School. The research problem consisted in identifying how the teaching of Corporal Adventure Practices can occur in Physical Education classes under the light of the critical-overcoming methodology and also in diagnosing the didactic-pedagogical resources necessary for this to occur. The general objective of this research was to develop a didactic-pedagogical sequence of the Corporal Adventure Practices based on the types of displacements proposed by Inácio et al (2016) that organizes them in sliding, walking / running, rolling and falling, in order to expand the knowledge of 6th grade students in a public school in Goiânia. It is an Action Research that used the formal PE classes as experimentation tools and for data collection: questionnaires, field diaries and iconographic records. The research revealed significant possibilities for teaching PCAs at school, including the use of the class sequencer as a strategy for class planning and the diversification of body adventure practices offered within a period of time. As limits, the scarcity of materials used can be presented.